Factors Determining Low Regional Financial Independence: Financial Autonomy and Degree of Decentralization - Agustina, Frida; Pramono, Agus Joko; Akbar, Bahrullah; Alma'arif, Alma'arif (Badan Pemeriksa Keuangan Republik Indonesia, 2022)
This study aims to assess the Tulang Bawang Regency's fiscal independence and determine the factors that affect it. This study used the data of the 2015-2019 Statement of Budget Realization of Tulang Bawang Barat Regency and primary data from interviews. The research method applies a qualitative approach with an inductive methodology using several financial ratios such as the effectiveness of Local Own-source Revenue management, the ratio of the degree of decentralization, the ratio of regional financial dependence, and the ratio of regional financial independence. Based on the results, the ratio of regional financial independence shows an average of 1.54%, within the 0-25% interval, and classified under the shallow criteria. It may be inferred that regional financial independence in meeting its funding needs for the administration of government affairs is still very low. The regional financial dependence ratio shows an average of 85.99%, categorized as a very high dependency. The calculation of the ratio results proves that the local own-source revenue of Tulang Bawang Barat Regency is still low. Furthermore, a large number of mandatory spending from the central government and national budgeting politics causes the regional financial independence of Tulang Bawang Barat Regency to become low.